Testing guidelines for connection of solar photovoltaic farm to distribution grid: The Malaysian experience - Yong, J.Y.; Ramachandaramurthy, V.K.; Tan, K.M.; Pouryekta, A.; Ekanayake, J.B.; Jayasinghe, A.E. (Wiley Online, 2020)
Solar photovoltaic technology is intermittent in nature and employs power converters for grid‐interconnection, which can bring stability and power quality (PQ) issues to the power grid. Therefore, a set of testing guidelines is required to assure that solar plants comply with the grid and inverter requirements. As such, this article presents comprehensive testing guidelines for the interconnection of solar systems into Malaysian power grid, including inverter and PQ tests. The test points, conditions, parameters and acceptable limits for both tests are discussed in detail. This article also presents the results of a case study in which the testing guidelines were applied to examine the PQ of an actual grid‐connected solar photovoltaic plant in Malaysia and to assess the performance of the smart inverter used in the tested solar system. The testing outcomes, which were recorded by a PQ analyser, showed that the tested solar system was in compliance with all the requirements stipulated in the testing guidelines. The findings presented in this article will help relevant parties to understand these solar testing guidelines and serve to promote the wide deployment of solar technology towards a clean and sustainable future.
Keywords: Electric Vehicles; Operational flexibility; Regulating reserve